2021
DOI: 10.1007/s00421-021-04815-0
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning of the muscle reduces the metaboreflex response of the knee extensors

Abstract: Purpose This study investigated the effect of ischemic preconditioning (IP) on metaboreflex activation following dynamic leg extension exercise in a group of healthy participants. Method Seventeen healthy participants were recruited. IP and SHAM treatments (3 × 5 min cuff occlusion at 220 mmHg or 20 mmHg, respectively) were administered in a randomized order to the upper part of exercising leg’s thigh only. Muscle pain intensity (MP) and pain pressure thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 82 publications
2
8
0
Order By: Relevance
“…One study found an attenuated hemodynamic response to metaboreflex activation during dynamic handgrip exercise preceded by IPC ( Mulliri et al, 2016 ), whereas another report did not show IPC to reduce hemodynamic responses or central muscle sympathetic nervous activity during activation of the metaboreflex ( Incognito et al, 2017 ). More recently, Angius et al (2022) corroborated the previously observed reduction in hemodynamic responses during metaboreflex activation using dynamic leg extension exercise. However, these authors also reported reduced end diastolic volumes following IPC which seems to indicate that altered hemodynamic responses during metaboreflex activation were due to blunted cardiac preload rather than discharge from group III/IV muscle afferents.…”
Section: Effect Of Ipc On Neurological and Perceptual Responses To Ex...supporting
confidence: 80%
See 1 more Smart Citation
“…One study found an attenuated hemodynamic response to metaboreflex activation during dynamic handgrip exercise preceded by IPC ( Mulliri et al, 2016 ), whereas another report did not show IPC to reduce hemodynamic responses or central muscle sympathetic nervous activity during activation of the metaboreflex ( Incognito et al, 2017 ). More recently, Angius et al (2022) corroborated the previously observed reduction in hemodynamic responses during metaboreflex activation using dynamic leg extension exercise. However, these authors also reported reduced end diastolic volumes following IPC which seems to indicate that altered hemodynamic responses during metaboreflex activation were due to blunted cardiac preload rather than discharge from group III/IV muscle afferents.…”
Section: Effect Of Ipc On Neurological and Perceptual Responses To Ex...supporting
confidence: 80%
“…Perhaps lending further support to the muscle afferent hypothesis is the evidence of IPC inducing hypoalgesic effects in humans. Indeed, previous investigations have demonstrated IPC techniques to reduce pressure pain ratings, pain under ischemia, perceived pain following eccentric exercise induced muscle damage, and time spent under pain during cold-water immersion tests ( Ferreira et al, 2016 ; Pereira et al, 2020 ; Slysz and Burr, 2021 ; Angius et al, 2022 ). IPC-induced hypoalgesia may be governed by endogenous substances that have antinociceptive effects on pain pathways.…”
Section: Effect Of Ipc On Neurological and Perceptual Responses To Ex...mentioning
confidence: 99%
“…Finally, we acknowledge that BP responses to PECO may have been lower because of mechanisms unrelated to the change in MVC. Ischemic preconditioning (brief cyclic bouts of limb ischemia and reperfusion) has been shown to reduce BP responses to PECO but not static exercise (58). Because exercise can elicit similar cardioprotective effects to ischemic preconditioning (59), the eccentric exercise bout may have induced a preconditioning effect and blunted the BP response to PECO.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore recommend, similarly to others [14, 29, 133], that researchers and clinicians instruct and familiarize their participants to rate their perception of effort specifically by excluding other exercise-related perception(s) from their sense of effort. This is also crucial for researchers investigating the perception of effort as a psychophysiological marker of the magnitude of the motor command [e.g., 88, 90] and using muscle pain as a psychophysiological marker of feedback from group III-IV muscle afferents [e.g., 136, 137].…”
Section: Discussionmentioning
confidence: 99%